QUANTUM COMPUTING: A NEW ERA FOR STUDENTS IN EDUCATION AND RESEARCH - Mohinur Raupova; Rano Ismoilova (Bright Mind Publishing, 2025)
Modern technologies and innovations are making an impact on all areas of our lives. Among them, quantum computing stands out as one of the most advanced and promising fields. While traditional computers have certain limitations, quantum computing offers the ability to reach new heights. Quantum computers can solve complex problems quickly and efficiently. The ability to perform multiple calculations simultaneously using qubits is increasing the demand for quantum technologies. Today's students have the opportunity to become future specialists who will develop and manage these technologies. For students studying English, mathematics, computer science, and physics, learning quantum computing technologies will not be difficult and will further enhance and deepen their understanding of these subjects. This article discusses the basic concepts of quantum computing, the opportunities it offers students in education and research, and its impact on society.
Keywords: Superposition, quantum entanglement, interference, qubit, Qiskit, Cirq, Q#, cryptography.